A Jew in the Roman bathhouse: cultural interaction in the ancient Mediterranean - Eliʾav, Yaron Zevi (Princeton University Press, 2023)
A provocative account of Jewish encounters with the public baths of ancient RomePublic bathhouses embodied the Roman way of life, from food and fashion to sculpture and sports. The most popular institution of the ancient Mediterranean world, the baths drew people of all backgrounds. They were places suffused with nudity, sex, and magic. A Jew in the Roman Bathhouse reveals how Jews navigated this space with ease and confidence, engaging with Roman bath culture rather than avoiding it.In this landmark interdisciplinary work of cultural history, Yaron Eliav uses the Roman bathhouse as a social laboratory to reexamine how Jews interacted with Graeco-Roman culture. He reconstructs their thoughts, feelings, and beliefs about the baths and the activities that took place there, documenting their pleasures as well as their anxieties and concerns. Archaeologists have excavated hundreds of bathhouse facilities across the Mediterranean. Graeco-Roman writers mention the bathhouse frequently, and rabbinic literature contains hundreds of references to the baths. Eliav draws on the archaeological and literary record to offer fresh perspective on the Jews of antiquity, developing a new model for the ways smaller and often weaker groups interact with large, dominant cultures.A compelling and richly evocative work of scholarship, A Jew in the Roman Bathhouse challenges us to rethink the relationship between Judaism and Graeco-Roman society, shedding new light on how cross-cultural engagement shaped Western civilization